Implementation of Computer Based Systems as Efficiency of Manager Decisions in Employee Reward - Maringan Sianturi (STMIK Budi Darma, 2019)
The purpose of this study is to provide support to management in determining employees who are entitled to employee reward based on competence using a computer-based system. Rewards for employees are aimed at motivating employees. The method used is the Preference Selection Index (PSI), which has the advantage of being able to produce criteria weight values without identifying using the weighting method.